Theoretical investigation of the contributions of the excitation forces to the vibration of an axial piston pump. (15th August 2019) - Ye, Shaogan; Zhang, Junhui; Xu, Bing; Zhu, Shiqiang; Xiang, Jiawei; Tang, Hesheng
Graphical abstract: Highlights: A theoretical dynamic model of an axial piston pump was developed. The excitation forces and the dynamic vibration can be accurately predicted. The contributions of excitation forces to the dynamic vibration were analyzed. The dominant excitation forces can be identified using the model. The vibrations are reduced by optimizing the bolt mounting positions. Abstract: A theoretical dynamic model of an axial piston pump was developed in this paper. The axial piston pump was modeled as a dynamic system with four masses and 19 degrees of freedom (DOFs). The dynamic excitation forces were calculated using the piston chamber pressures simulated with a three-dimensional computational fluid dynamics (CFD) model. A test rig was constructed to validate both the CFD model and the dynamic model. The CFD model was validated by a comparison of the discharge pressure ripples, and the dynamic model was validated by a comparison of the vibration velocities. The vibration characteristics and the contributions of the excitation forces to the vibrations of the housing were analyzed. The results demonstrated that the vibration velocity along the X F - axis is larger than the vibration velocities along the Y F - and Z F - axes, and the vibration angular velocity around the X F - axis is smaller than that around the Y F - axis. The excitation moments of forces M CY and M PY have large contributions to most of the vibrations, and the excitation moments of forces M CX and M PX have negligible contributions to most of the vibrations. In addition, the vibrations are found to be significantly reduced by optimizing the bolt mounting positions.